2009
DOI: 10.1521/soco.2009.27.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining a Positive Self-Image by Stereotyping Others: Self-Threat and the Stereotype Content Model

Abstract: The present study examines how target group’s stereotype content (on warmth and competence dimensions) influences subsequent target evaluation following self-threat related to one’s competence. Participants first received threatening or non-threatening feedback on their competence. They evaluated then a job candidate who was stereotyped either as competent and cold (Asian) or as warm and incompetent (working mother). As predicted, threatened participants derogated only the Asian target on her perceived warmth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 25 publications
1
36
1
1
Order By: Relevance
“…Collange, Fiske, & Sanitioso, 2009;Fiske & Neuberg, 1990;Leyens & Yzerbyt, 1992;Petty & Cacioppo, 1986). This perspective is yet to be developed in research on responses to norm deviants.…”
Section: Information Processing and The Black-sheep Effectmentioning
confidence: 99%
“…Collange, Fiske, & Sanitioso, 2009;Fiske & Neuberg, 1990;Leyens & Yzerbyt, 1992;Petty & Cacioppo, 1986). This perspective is yet to be developed in research on responses to norm deviants.…”
Section: Information Processing and The Black-sheep Effectmentioning
confidence: 99%
“…Because people are reluctant to utilize stereotypes, stereotype use will often be resisted in positive or benign environments. When threats to the self or ingroup are seen as particularly close, imminent, or large in magnitude, however, individuals are more likely to utilize stereotypes (e.g., Collange, Fiske, & Sanitioso, 2009;Fein & Spencer, 1997;Govurun, Fuegen, & Payne, 2006;Spencer, Fein, Wolfe, Fong, & Dunn, 1998). We argue, however, that threat will not lead to increased stereotype utilization for all individuals; rather, it depends on the relevance of the threat to a perceiver's dominant motivational concern.…”
Section: Responding To Stereotype-based Threatsmentioning
confidence: 67%
“…While many studies have examined the motivation to avoid stereotype use and the means by which stereotyping is avoided and down-regulated (e.g., Kawakami, Dovidio, Moll, Hermsen, & Russin, 2000;Monteith, Ashburn-Nardo, Voils, & Czopp, 2002;Moskowitz, et al, 2000;Plant & Devine, 1998), a growing body of research has identified conditions under which motives lead to increased stereotyping (e.g., Collange, Fiske, & Sanitioso, 2009;Fein & Spencer, 1997;Govorun et al, 2006;Spencer, Fein, Wolfe, Fong & Dunn, 1998). The present studies add to this literature to illustrate how specific stereotypical information is utilized to meet immediate self-regulatory goals and needs.…”
Section: Implications For Research On Stereotypingmentioning
confidence: 85%
See 1 more Smart Citation
“…La competencia se relaciona con la inteligencia, eficacia y destreza mientras que la calidez se relaciona con la amabilidad, honradez o bondad. La percepción de ambos elementos indica hasta qué punto un elemento es respetado y apreciado, respectivamente (Collange, Fiske, & Sanitioso, 2009). Se considera también que la primacía de la dimensión de calidez frente a la de competencia tiene un valor funcional: las personas deben determinar las intenciones de los otros y su capacidad para ponerlas en práctica para sobrevivir en las interacciones sociales (Fiske Cuddy, & Glick 2007).…”
Section: Introductionunclassified